Illness perceptions and affective symptoms: Predictors of self‐management behaviors in mild cognitive impairment: Dementia care research (research projects; nonpharmacological) / Assessment and care planning. (7th December 2020) - Kim, Hyejin; Sereika, Susan M; Bender, Catherine; Albert, Steven; Lingler, Jennifer
Abstract: Background: Although a recent guideline on mild cognitive impairment (MCI) recommends non‐pharmacological interventions (i.e., self‐management behaviors such as exercise and cognitive training) for the management of MCI, predictors of such behaviors have not been identified in this population. We explored predictors of four categories of self‐management behaviors (i.e., physical activity, cognitive‐enhancing medication, mental activity, and vitamin/herbal supplements) in persons with MCI (PwMCI). Methods: Using a cross‐sectional design, we conducted a secondary analysis pooling two existing datasets. We examined the predictive role of perceptual factors (i.e., individuals' perceived understanding of MCI and its cause), affective symptoms (i.e., anxiety and depression), and clinical/sociodemographic factors. We also measured the total number of (range: 0‐4), and performance of each ('yes' or 'no') of the four categories of self‐management behaviors. We performed hierarchical linear (for the total number of self‐management behaviors) and binary logistic (for each self‐management behavior) regression analyses, controlling for age, sex, years of education, and the number of comorbid conditions as potential covariates. Results: Participants (N=137) were on average 71.5 years old with 16.1 years of education. Most were Caucasian (92.0%) and diagnosed with amnestic MCI (82.5%). Although we did not find any main effects of predictors, some interactions were significant through further model expansion. Better performance of self‐management behaviors was associated with 1) lower levels of perceived understanding of MCI in men ( b = ‐0.090, =.037), and 2) lower levels of anxiety symptoms in Caucasian participants ( b = ‐0.206, p =.049). In hierarchical logistic regression analyses, higher levels of perceived understanding of MCI were associated with the better performance of physical (OR=0.942, 95%CI=[0.898, 0.980]) and mental (OR=0.959, 95% CI=[0.922, 0.998]) activities among participants with lower levels of education. Among participants with more years of education, higher levels of perceived understanding of MCI were associated with better adherence to cognitive‐enhancing medication (OR=1.043, 95% CI=[1.002, 1.085]), and more anxiety symptoms were associated with better performance of mental activity (OR=1.048, 95% CI=[1.003, 1.095]). Conclusion: Our findings suggest that perceived understanding of MCI, levels of anxiety, and demographic factors should be considered together when evaluating the performance of self‐management behaviors to prevent or delay further cognitive changes among PwMCI.